''Bonaparte ne chevauchait en personne entre les lignes de tir et les troupes et attisait le courage dans les coeurs'' - Smolej, Mojca (Linguistica (Ljubljana), 2018)
In this article we focus on the influence of French on the military vocabulary of Lublanske novice (Ljubljana News; 1791 - 1800), the first Slovene newspaper. The analysis reveals that in the articles published in this newspaper Valentin Vodnik laid the foundation of Slovene military terminology. He reported on military events from the colonial world and accurately cited developments during the Napoleonic Wars. Vodnik's military language is untypical in that it is replete with expressive words and phrases as well as with various rhetorical figures, and as such has a literary or poetic quality. In addition to the somewhat poetic descriptions of warfare, it is necessary to draw attention to Vodnik's military vocabulary which is mostly of German and French origin. However, in the present article, we focus only on the vocabulary which could have came into Slovene from French (possibly via German). Since it is difficult to find out with Vodnik's articles whether we are dealing with jargonisms, terms or general lexis, we compare his military vocabulary with that of the first Slovene military dictionary compiled by Andrej Komel in 1872. The comparison shows to what extent Vodnik's military vocabulary was taken over into Slovene military terminology, as far as it can be gathered from Komel's work.
Keywords: 1791-1800; francoščina; jeziki v stiku; Ljubljanske novice (periodika); slovenščina; Vodnik, Valentin; vojaško besedišče; vojni besednjak